A novel hypopigmentation for southeast Pacific humpback whales - Avila, Isabel; Castro, Cristina (J. Cetacean Res. Manage., 2024)
Southeast Pacific humpback whales (Megaptera novaeangliae) migrate annually to breeding grounds in Machalilla, Ecuador, and Uramba Bahía Málaga, Colombia. This species usually displays a black/ grey body colouration with its dorsal and caudal fins exposed above water. Between 2005 and 2023, whales in these regions were studied and photographed on 1,627 days. Results indicated that 29 whales have novel body markings, including white spots, irregular circles and sinuous lines, which resemble the paintings of 20th Century artist Jackson Pollock. While this novel ‘Pollock‐style’ pigmentation does not appear to cause health problems, we recommend further studies to evaluate its origin and effects.